Analysis of aflatoxins and ergot alkaloids in feeds for adult equine (Research, Society and Development, 2021)
Mycotoxins are products resulting from fungi metabolism normally present in the environment and which can develop in food. The aim of this study was the fungi quantification, aflatoxin detection and investigation of ergot alkaloids occurrence in pelleted feed for adult equines during storage. The feed samples were collected from three rural properties with equideoculture activity in the city of Teresina, Piauí, Brazil. The results showed that was no significant difference (p